Culturally Appropriate Instrument: A Systematic Literature Review - Herlina Siwi Widiana (Universitas Ahmad Dahlan, 2021)
Culture has an impact on the presentation of mental health problems. Variation in symptoms, the existence of local idioms, and etiology were found in different target groups. Therefore a culturally appropriate instrument is needed to assess mental health problems for a specific target group. This study aimed to explore the literature on developing a culturally appropriate instrument. A systematic literature review was conducted through the Web of Science Core Collection database search engine. The keywords applied for searching were depression, mental health, screening tool, scale, instrument, measure, assess, and culture. Only articles published in English were selected, which resulted in 8,113 articles. Refining the results was conducted based on several categories, resulted in 4,351 articles. The titles, abstracts, and main texts were then read. As a result, a final set of 33 articles was selected from a comprehensive review. A culturally appropriate instrument was developed by deriving items from experience and authoritative knowledge and then validating psychometric properties. Local idioms, symptoms, and constructs were colored the culturally appropriate instruments for specific target groups.